126 Regulation of initiation of follicle growth and dynamics of early follicular development in the sheep. (7th December 2018) - Monniaux, D; Cadoret, V; Clément, F; Fabre, S; Locatelli, Y; Monget, P; Dalbies-Tran, R
Abstract: Primordial follicles embedded in the ovarian cortex are the source of developing follicles. Follicle growth activation and development up to the small antral follicle stage are controlled by cell interactions. The sheep ovary offers an appropriate non-rodent model to study these interactions, thanks to the development of in vitro and in vivo experimental approaches, ex vivo molecular analyses and in silico mathematical modeling. Each primordial follicle, composed of an oocyte surrounded by a single layer of quiescent granulosa cells, relies on nutrients and growth factors supplied by the surrounding stroma of connective tissue. In vitro cultures of ovarian cortex have shown that primordial follicles are activated by the lifting of mechanisms maintaining quiescence, some of them involving AMH secreted by already growing follicles. Afterwards, follicle development is supported by a finely tuned molecular dialog between the growing oocyte and proliferating granulosa cells. The isolation of preantral follicles and their development in vitro as individual follicles perturb this dialog, leading to an acceleration of follicular maturation. In vivo, mutations in the oocyte factors BMP15, GDF9 or their receptor BMPR1B also impair this dialog, leading to an imbalance between oocyte growth and cell proliferation, which can be reproduced by models for cell dynamics. During the growth of preantral follicles, the recruitment and differentiation of theca cells from the ovarian stroma provide them with a structural and vascularized support. In vivo exposure of sheep fetal ovaries to testosterone imprints the stroma cells so that the expression of genes involved in extracellular matrix organization and cell-cell adhesion is affected in theca at adulthood; this leads to a lower ovarian tissue rigidity that can account for the accelerated follicle growth observed in androgenized ewes. A better knowledge of cell interactions during early follicular development will help to improve the biotechnology methods of fertility preservation.